Six-Year Retrospective Review of Hospital Data on Antimicrobial Resistance Profile of Staphylococcus aureus Isolated from Skin Infections from a Single Institution in Greece - Christina Stefanaki; Alexandra Ieronymaki; Theoni Matoula; Chrysseis Caroni; Evaggelia Polythodoraki; Stella-Eugenia Chryssou; George Kontochristopoulos; Christina Antoniou (MDPI AG, 2017)
Objective: To determine the prevalence of resistant strains of Staphylococcus aureus (S. aureus) isolated from Skin and soft tissue infections (SSTI) to various antibiotics. Material and Methods: All culture-positive results for S. aureus from swabs taken from patients presenting at one Greek hospital with a skin infection between the years 2010-2015 were examined retrospectively. Bacterial cultures, identification of S. aureus and antimicrobial susceptibility testing were performed using the disk diffusion method according to Clinical and Laboratory Standards Institute (CLSI) guidelines and European Committee on Antimicrobial testing (EUCAST) breakpoints. EUCAST breakpoints were applied if no CLSI were available. Results: Of 2069 S. aureus isolates identified, 1845 (88%) were resistant to one or more antibiotics. The highest resistance was observed for benzylpenicillin (71.9%), followed by erythromycin (34.3%). Resistant strains to cefoxitin defined as MRSA (methicillin-resistant S. aureus) represented 21% of total isolates. Interestingly, resistance to fusidic acid was 22.9% and to mupirocin as high as 12.7%. Low rates were observed for minocycline, rifampicin and trimethoprim/sulfamethoxazole (SXT). Resistance to antibiotics remained relatively stable throughout the six-year period, with the exception of cefoxitin, fusidic acid and SXT. A high percentage of MRSA strains were resistant to erythromycin (60%), fusidic acid (46%), clindamycin (38%) and tetracycline (35.5%). Conclusions: Special attention is required in prescribing appropriate antibiotic therapeutic regimens, particularly for MRSA. These data on the susceptibility of S. aureus may be useful for guiding antibiotic treatment.